1986
DOI: 10.1152/ajpgi.1986.250.5.g561
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of intestinal calcium transport across the rat intestine

Abstract: Kinetic analysis of transmural calcium transport, as evaluated by in situ intestinal loops, has confirmed the existence of two transport processes, a saturable, transcellular one that is regulated by vitamin D and predominates in the proximal intestine and a nonsaturable process similar in intensity throughout the intestine. Transport data obtained from everted sac experiments are kinetically consistent with events in the in situ loop. Analysis of the three component steps making up the saturable process, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
173
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(182 citation statements)
references
References 0 publications
9
173
0
Order By: Relevance
“…Calcium absorption efficiency is increased by 1,25(OH) 2 D 3 . Based on a mathematical evaluation of available protein and transport data, Bronner et al (2) argued that the rate-limiting step in this process was the vitamin D-dependent production of the intracellular calcium ferry, calbindin D 9k . In addition, some studies, including our own in Caco-2 cells (32), have suggested that the cellular level of the nVDR is a critical determinant of vitamin D responses in the enterocyte.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Calcium absorption efficiency is increased by 1,25(OH) 2 D 3 . Based on a mathematical evaluation of available protein and transport data, Bronner et al (2) argued that the rate-limiting step in this process was the vitamin D-dependent production of the intracellular calcium ferry, calbindin D 9k . In addition, some studies, including our own in Caco-2 cells (32), have suggested that the cellular level of the nVDR is a critical determinant of vitamin D responses in the enterocyte.…”
Section: Discussionmentioning
confidence: 99%
“…However, while calbindin D 28k remained elevated for 32 h after its peak induction, a high rate of calcium absorption was not maintained during that same period, falling to 25% of its maximum rate. Using di-and trihomoanalogs of 1,25(OH) 2 Values are means Ϯ SE from 3 independent experiments (n ϭ 9 observations/treatment). Values within a column with different letter superscripts are significantly different from one another (Fisher's protected LSD; P Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1; Hoenderop et al 2000b;Wasserman and Fullmer 1995). Active absorption of dietary Ca 2+ occurs primarily in the proximal small intestine, while in kidney active Ca 2+ reabsorption is restricted to the distal convoluted tubule (DCT) and the connecting tubule (CNT; Bronner et al 1986;Friedman and Gesek 1995).…”
Section: Introductionmentioning
confidence: 99%